ESTIMATING DIVERSION RATIOS IN HOSPITAL MERGERS. (24th July 2019) - Rossi, Cecilia; Whitehouse, Russell; Moore, Alex
ABSTRACT: Understanding patient choice is vital in assessing the closeness of competition between hospitals. The standard technique used in the UK is to estimate substitution patterns based on historical general practitioner (GP) referrals. In this paper we compare the results of the 'GP referral' methodology to a demand estimation approach. Using patient-level data over a 3-year period (2012/13–2014/15) we apply both methodologies to every hypothetical merger between hospitals in England, for three specialties. We find a high degree of consistency between the two approaches, suggesting that GP referral analysis is a useful and reliable filter in merger cases. There are a small number of cases, however, in which the GP referral approach filters out potentially problematic mergers. This is particularly true for 'borderline' cases. Filtering should therefore be done with caution and in conjunction with additional evidence.